RNA-Seq Analysis Reveals the Potential Molecular Mechanisms of Puerarin on Intramuscular Fat Deposition in Heat-Stressed Beef Cattle - Chen, Huan; Peng, Tao; Shang, Hanle; Shang, Xianglong; Zhao, Xianghui; Qu, Mingren; Song, Xiaozhen (Frontiers in Nutrition, 2022)
To investigate the effect of Puerarin on intramuscular fat deposition in heat-stressed beef cattle and its underlying mechanism. Thirty-two healthy Jinjiang bulls were randomly divided into four groups and dietary with 0 (Control), 200 (Pue200), 400 (Pue400), and 800 (Pue800) mg/kg Puerarin in the feed concentrate. The results showed that Puerarin treatment enhanced the concentration of crude fat, fatty acid (C14:1 and C17:1), and the activity of fatty acid synthase in Longissimus thoracis (LT), but decreased the levels of blood leptin (P < 0.05). High-throughput sequencing of mRNA technology (RNA-Seq) was used and the analysis showed that 492 genes were down-regulated and 341 genes were up-regulated in LT, and these genes were significantly enriched to the pathways related to lipid metabolism. These results indicated that dietary supplemental with Puerarin enhanced intramuscular fat deposition by regulating lipid metabolism of heat-stressed beef cattle.